2011
DOI: 10.1042/bsr20110002
|View full text |Cite
|
Sign up to set email alerts
|

The harmala alkaloid harmine is a modulator of circadian Bmal1 transcription

Abstract: Biological rhythms are orchestrated by a cell-autonomous clock system that drives the rhythmic cascade of clock genes. We established an assay system using NIH 3T3 cells stably expressing the Bmal1 promoter-driven luciferase reporter gene and used it to analyse circadian oscillation of the gene. Modulators of PKC (protein kinase C) revealed that an activator and an inhibitor represented short- and long-period phenotypes respectively which were consistent with reported effects of PKC on the circadian clock and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 37 publications
1
37
0
2
Order By: Relevance
“…Recently, we found that the herbal alkaloid, harmine has potential as anti-inflammatory agents that can suppress TNF-α and NO production [10]. We also found using a customdesigned assay for circadian oscillation in vitro that harmine extends the circadian period [11]. The Amaryllidaceae alkaloid, lycorine (3, 12-didehydro-9, 10-[methylenebis(oxy)]-galanthan-1α, 2β-diol) also suppressed TNF-α and NO production, indicating powerful anti-inflammatory activity [10].…”
Section: Introductionmentioning
confidence: 91%
“…Recently, we found that the herbal alkaloid, harmine has potential as anti-inflammatory agents that can suppress TNF-α and NO production [10]. We also found using a customdesigned assay for circadian oscillation in vitro that harmine extends the circadian period [11]. The Amaryllidaceae alkaloid, lycorine (3, 12-didehydro-9, 10-[methylenebis(oxy)]-galanthan-1α, 2β-diol) also suppressed TNF-α and NO production, indicating powerful anti-inflammatory activity [10].…”
Section: Introductionmentioning
confidence: 91%
“…15) It is possible that the effect of harmine on the endogenous Bmal1 expression cannot be mimicked by the promoter activity of a minimal region we previously demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…14) We previously reported that harmine dose-dependently lengthens the circadian period in NIH 3T3 cells. 15) However, several studies have demonstrated that the signals that are input into the circadian clock in the SCN considerably differ from those input into peripheral cells. 1,2,22) Thus, how harmine affects the master clock in the SCN is critical to understand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Harmine is widely distributed in nature, such as in various plants, marine creatures, insects, mammalians, human tissues and body fluids. Harmine have antimicrobial, antiplasmodial, antifungal, antioxidative, antitumor, antimutagenic, cytotoxic and hallucinogenic properties [1][2][3][4][5][6][7] . Beta-carboline compounds act as inverse agonists at the benzodiazepine site of the gammaaminobutyric acid type A receptors and have actions entirely opposite to those of the anxiolytic benzodiazepines.…”
Section: Introductionmentioning
confidence: 99%